A sensorless force-feedback system for robot-assisted laparoscopic surgery. (1st October 2019) - Zhao, Baoliang; Nelson, Carl A.
Abstract: The existing surgical robots for laparoscopic surgery offer no or limited force feedback, and there are many problems for the traditional sensor-based solutions. This paper builds a teleoperation surgical system and validates the effectiveness of sensorless force feedback. The tool-tissue interaction force at the surgical grasper tip is estimated using the driving motor's current, and fed back to the master robot with position-force bilateral control algorithm. The stiffness differentiation experiment and tumor detection experiment were conducted. In the stiffness differentiation experiment, 43 out of 45 pairs of ranking relationships were identified correctly, yielding a success rate of 96%. In the tumor detection experiment, 4 out of 5 participants identified the correct tumor location with force feedback, yielding a success rate of 80%. The proposed sensorless force-feedback system for robot-assisted laparoscopic surgery can help surgeons regain tactile information and distinguish between the healthy and cancerous tissue.